2022
DOI: 10.3390/life12071026
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Urolithiatic Activity of Aqueous and Ethanolic Extracts from Saussurea costus (Falc) Lispich Using Scanning Electron Microscopy

Abstract: The plant Saussurea costus (Falc) Lipsch has many biological activities and a strong curative and preventive power against a variety of diseases including cancer, diabetes, and hemorrhoids. In the current study, phytochemical screening was carried out as well as an investigation of the antilithiatic and antioxidant activities of aqueous and ethanolic extracts of this plant. The results showed that aqueous and ethanolic extracts were effective in reducing cystine stone mass and that the aqueous extract of Sauss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Various studies have shown that chemical compound concentrations vary depending on different factors, which include the solvent used in plant extracts, the area of plants grown, and the quantity of the plant used [ 44 ]. The active constituents of this well-known medicinal plant are mostly terpenes, with various levels of flavonoids, anthraquinones, alkaloids, tannins, and inulin, as described in earlier research [ 45 ]. Several laboratory experiments and animal model studies have indicated that Saussurea costus possesses anti-inflammatory, antitrypanosomal, and anti-malignant tumor effects, confirming its extended use in medicine [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown that chemical compound concentrations vary depending on different factors, which include the solvent used in plant extracts, the area of plants grown, and the quantity of the plant used [ 44 ]. The active constituents of this well-known medicinal plant are mostly terpenes, with various levels of flavonoids, anthraquinones, alkaloids, tannins, and inulin, as described in earlier research [ 45 ]. Several laboratory experiments and animal model studies have indicated that Saussurea costus possesses anti-inflammatory, antitrypanosomal, and anti-malignant tumor effects, confirming its extended use in medicine [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Saussurea costus plant is frequently employed in traditional therapies. It also has numerous bioactivities, such as antimicrobial, antilithiatic, and antioxidant properties, and a potent ability to treat and prevent a wide range of illnesses, such as cancer, diabetes, and hemorrhoids [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the GC-MS analysis; our previous work [ 20 ] on the same extracts revealed that they were composed of the following: caryophyllene oxide, 1,3-propanediol, 2-(hydroxymethyl)-2-nitro, dihydrodehydrocostus lactone, quercetin, cyclodecacyclotetradecene and dehydrocostuslactone for the ethanolic extract of S. costus ; 9,12,15-octadecatrienoic acid,(z,z),alpha guaiene,2(3H)-benzofuranone,6-ethenythexhydroxy, Cholest-7-en-3-ol,4-methyl-,3.beta,4.alpha and cyclodecacyclotetradecene,14,15-didehydroxy for the aqueous extract of S. costus .…”
Section: Discussionmentioning
confidence: 99%
“…S. costus is an herbaceous plant of the Asteraceae family native to Asia which has been used to treat various pathologies in traditional medicine [ 17 , 18 , 19 ]. It contains several molecules, including quercitrin flavonoids and alkaloids ( Figure 1 ), with activities against calcium oxalate type urinary lithiasis [ 20 ]. Although it is used as a popular remedy for kidney stones [ 18 ], its efficacy and mechanism as an anti-struvite, antimicrobial and anti-inflammatory agent are still unknown.…”
Section: Introductionmentioning
confidence: 99%